Public Preferences for Mental Health Initiatives to Prevent Crime - Mancini, Christina (Criminal justice review, 2025)
Recently, in the wake of high-profile incidents, public and policy attention has been directed toward addressing mental health as an avenue to prevent crime. Given the link between public opinion and policy, it is important to understand how the public views such efforts. Specifically, do Americans favor measures (e.g., diversion/mental health partnerships, 988 hotline) that require a mental health, rather than police response, for incidents involving mentally distressed people? What factors—concerning beliefs about crime and mental health and personal characteristics (e.g., prior mental health history)—are associated with these policy preferences? Drawing on a 2022 national poll, this study examines these research questions. Results suggest majority approval for changes in mental health responses to crime among the public. However, divides in public attitudes are evident.